2017
DOI: 10.1002/micr.30174
|View full text |Cite
|
Sign up to set email alerts
|

Partial tibial nerve transfer to tibialis anterior for traumatic peroneal nerve palsy

Abstract: This series provides good evidence that this evolving reconstructive technique may achieve excellent results and should be considered in traumatic common peroneal nerve injuries that would traditionally rely on conventional nerve grafting alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 21 publications
(41 reference statements)
0
30
0
Order By: Relevance
“…Given that only 20% of a muscle's axons are needed to produce normal function, partial nerve transfer can reinnervate a target while maintaining donor motor function. Although restoration of dorsiflexion via nerve transfer (Ferris & Maciburko, 2017;Flores, Martins, & Siqueira, 2013;Giuffre, Bishop, Spinner, Levy, & Shin, 2012;Leclère, Badur, Mathys, & Vögelin, 2015;Nath, Lyons, & Paizi, 2008) has been documented in adults, outcomes are limited, success is variable, and recent systematic review of these procedures demonstrated a bimodal distribution with regards to recovery of dorsiflexion-with a majority either demonstrating MRC 0 or 4 strength postoperatively (Head et al, 2019). The application of nerve transfer to lower extremity reconstruction is uncommon and its utility is evolving.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that only 20% of a muscle's axons are needed to produce normal function, partial nerve transfer can reinnervate a target while maintaining donor motor function. Although restoration of dorsiflexion via nerve transfer (Ferris & Maciburko, 2017;Flores, Martins, & Siqueira, 2013;Giuffre, Bishop, Spinner, Levy, & Shin, 2012;Leclère, Badur, Mathys, & Vögelin, 2015;Nath, Lyons, & Paizi, 2008) has been documented in adults, outcomes are limited, success is variable, and recent systematic review of these procedures demonstrated a bimodal distribution with regards to recovery of dorsiflexion-with a majority either demonstrating MRC 0 or 4 strength postoperatively (Head et al, 2019). The application of nerve transfer to lower extremity reconstruction is uncommon and its utility is evolving.…”
Section: Discussionmentioning
confidence: 99%
“…We avoided branches to soleus (Ferris & Maciburko, 2017;Flores et al, 2013;Pirela-Cruz, Hansen, Terreros, Rossum, & West, 2009), gastrocnemius (Flores et al, 2013;Giuffre et al, 2012), and tibialis posterior as their sacrifice could weaken "push-off," interfere with the option of subsequent tendon transfer, provide limited donor nerve length, and activate out of phase and antagonistic to TA function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some centers perform nerve transfer of tibial nerve branches to branches to the tibialis anterior in cases of peroneal nerve injury. 2,11 Understanding the topographical organization of the tibial nerve is also important in these cases. These nerve transfers are typically performed at the level of branches of the tibial nerve, typically using branches to the flexor digitorum longus, flexor hallucis longus, or soleus.…”
Section: Discussionmentioning
confidence: 99%
“…In combining the four studies we were able to identify in the literature, 35 total patients underwent tibial nerve transfer for CPN palsy, of which 21 obtained an MRC grade of 3 or higher for dorsiflexion. [59][60][61][62] Posterior Tibialis Tendon Transfer PTTT is a reliable salvage treatment option in the setting of failed nerve-saving procedures or delayed treatment. The posterior tibialis tendon is transferred to the dorsum of the foot either by attachment on the medial cuneiform or the tibialis anterior tendon itself.…”
Section: Nerve Grafting and Nerve Transfermentioning
confidence: 99%